2021
DOI: 10.1177/0300891621992428
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy after testis-sparing surgery for seminoma in monorchid patients: safety and efficacy

Abstract: Purpose: To evaluate local control and longitudinal endocrine data in monorchid patients treated with testicular-sparing surgery and adjuvant radiotherapy (RT) for seminomatous germ-cell tumors. Methods: We searched our database established in 2009 for patients with seminoma who received testis irradiation following partial orchiectomy up to 2018. Eleven patients were identified. All had associated germ cell neoplasia in situ (GCNIS) in surrounding parenchyma. Analysis focused on local control and testosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The presence of GCNIS in a testis carries an estimated risk of evolving into invasive disease of 50% within 5 years and 70% within 7 years [ 44 ]. Therefore, it is necessary to consider local radiotherapy for patients with GCNIS, particularly for those with a solitary testis [ 45 , 46 , 47 ]. In Avuzzi et al’s study, radiotherapy following testicular-sparing surgery showed no local or distant relapses in a medium-term follow-up, with hormonal function preserved in about 54.5% of patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of GCNIS in a testis carries an estimated risk of evolving into invasive disease of 50% within 5 years and 70% within 7 years [ 44 ]. Therefore, it is necessary to consider local radiotherapy for patients with GCNIS, particularly for those with a solitary testis [ 45 , 46 , 47 ]. In Avuzzi et al’s study, radiotherapy following testicular-sparing surgery showed no local or distant relapses in a medium-term follow-up, with hormonal function preserved in about 54.5% of patients.…”
Section: Resultsmentioning
confidence: 99%
“…In Avuzzi et al’s study, radiotherapy following testicular-sparing surgery showed no local or distant relapses in a medium-term follow-up, with hormonal function preserved in about 54.5% of patients. Associations were noted between baseline testosterone levels, tumor size, and risk of exogenous androgen replacement [ 46 ]. Dieckmann et al highlight that 18–20 Gy local radiotherapy eradicates the majority of GCNIS.…”
Section: Resultsmentioning
confidence: 99%